BUN‐to‐ALB ratio as an effective predictor of 30 day mortality in ADHF patients in eastern China - Xin Huang; Chao Wang; Shiming He; Guoan Jian; Kun Jiang; Zihao Lu; Guotai Sheng; Yang Zou; Guobo Xie (ESC Heart Failure)
Abstract Aims The blood urea nitrogen‐to‐albumin ratio (BAR) is considered a potential indicator for assessing the poor prognosis of heart failure (HF). However, its prognostic value for Chinese patients with acute decompensated HF (ADHF) remains unclear. Methods This study included ADHF patients who met the study criteria and were admitted to Jiangxi Provincial People's Hospital from 2019 to 2022. We first employed univariate and multivariate Cox regression models to determine the role of BAR in evaluating the short‐term prognosis of ADHF patients. Subsequently, we used restricted cubic spline regression to explore the nonlinear relationship and potential threshold between BAR and prognosis. Receiver operating characteristic (ROC) curve analysis was performed to calculate the predictive accuracy of BAR for 30 day mortality and identify relevant threshold points. Results A total of 1421 patients were included in the analysis, and the population was divided into two groups based on the optimal threshold for BAR (0.33) determined by ROC curve analysis. During the median 30 day follow‐up period, the mortality rates in the high‐BAR and low‐BAR groups were 12.46% and 1.26%, respectively. Multivariable Cox regression analysis indicated that a high BAR was associated with an increased 30 day mortality risk in ADHF patients [hazard ratio (HR): 3.25, 95% confidence interval (CI): 1.28–8.30], particularly among those with concomitant cerebral infarction (HR: 19.12, 95% CI: 2.67–136.67). The five sensitivity analyses completed were consistent with the results of the main analysis. Furthermore, restricted cubic spline analysis revealed a nonlinear association between BAR and short‐term mortality in ADHF patients (P for nonlinearity: <0.001), with a potential threshold effect observed when BAR was between 0.3 and 0.5. ROC curve analysis determined that the predictive efficiency of BAR for short‐term mortality in ADHF patients was ~84%, with an area under the ROC curve (AUC) of 0.84. Conclusions This study found that BAR can serve as an effective predictor of short‐term prognosis in ADHF patients based on clinical data from the Jiangxi population, with an optimal predictive threshold calculated at 0.33.